Human β2-glycoprotein I attenuates mouse intestinal ischemia/reperfusion induced injury and inflammation - Tomasi, Maurizio; Hiromasa, Yasuaki; Pope, Michael R.; Gudlur, Sushanth; Tomich, John M.; Fleming, Sherry D. (My University, 2013)
Intestinal ischemia-reperfusion (IR)-induced injury results from a complex cascade of inflammatory components. In the mouse model of intestinal IR, the serum protein, β2-glycoprotein I (β2-GPI) binds to the cell surface early in the cascade. The bound β2-GPI undergoes a conformational change which exposes a neoantigen recognized by naturally occurring antibodies and initiates the complement cascade. We hypothesized that providing additional antigen with exogenous β2-GPI would alter IR-induced tissue injury. Administration of human but not mouse β2-GPI attenuated IR-induced tissue damage and prostaglandin E[subscript 2] production indicating a physiological difference between β2-GPI isolated from the two species. To investigate whether structural features were responsible for this physiological difference, we compared the chemical, physical and biochemical properties of the two proteins. Despite possessing 76% amino acid identity and 86% sequence homology, we found that mouse β2-GPI differs from the human protein in size, carbohydrate chain location, heterogeneity and secondary structural content. These data suggest that the structural differences result in mouse Ab recognition of soluble human but not mouse β2-GPI and attenuated IR-induced injury. We conclude that caution should be exercised in interpreting results obtained by using human β2-GPI in a mouse model.
Keywords: Apolipoprotein H; Prostaglandin E2; Mouse; Ischemia